Analisis Minat Pada STIE Kesatuan Bogor Dengan Pendekatan Motivasi, Kepribadian Dan Karakteristik Wirausahawan - Mekaniwati, Ani; Setiana, Anna (Jurnal Ilmiah Manajemen Kesatuan, 2018)
In developed countries the interest to become entrepreneurs is quite large, helping patterns that exist in developed countries where they no longer want to be lower-level people to become entrepreneurs in areas of their interest. The country's economy can be built by growing business in various fields, namely by creating new jobs through entrepreneurship In this case the Higher Education can be a place to foster and motivate students to have the courage and interest to become an entrepreneur. The problem faced by universities is how to foster interest in entrepreneurship to students so that their chosen career choice after graduation is as entrepreneurs.This study was conducted to measure entrepreneurship interest of STIE Kesatuan Bogor students and to find the the factors that affect such interest from motivation, skills, and education point of views. Survey with questionnaire was the data gathering method and Structural Equation Modeling was deployed for main analysis and diagonal analysis (Suharjo Split) is used to measure the level of interest and the level of interest of STIEK Bogor students for entrepreneurs